Aspectos materiais, processuais e procedimentais da ação civil por improbidade administrativa - Abrão Filho, Gabriel (2007)
That study had like objective the analysis of the some aspects of material, procedural and procedural right brought by Law 8.429/92. The relevance of the choice of the subject is unquestionable, sufficiency be attacked for the relative events to the acts of the Public Administration in the last decade and, more precisely, in the two last years of the national political setting. The society has the right to the installment of you count of the acts of the public agents, supported that is for the international and national legislation, by the idea of that the necessary, public force for the guarantee of the rights of the man and of the citizen is instituted for fruition by everybody and not for private utility of those to who is trusted. The Brazilian society looks that awoke for the reality of that what is public is of everybody and those in who trusted and, however, betrayed that confidence, should be made responsible and take responsibility for that. The present study it is divided in four parts, where they had been identified and distinguished the acts that characterize the administrative improbity, as well as the principles mortally wounded by this civil behavior, sanctions and the criminal guardianship of the improbity, the analysis of the administrative procedures and the civil inquiry and the study of aspects of the action at law and the special procedure brought by the Law of Administrative Improbity